Does preoperative atrial fibrillation essentially influence on early results of patients undergoing cardiosurgery procedures due to mitral valve regurgitation? - Bańkowski, Tomasz; Marczak, Jakub; Waliszewska, Marta; Pelczar, Marek; Jakubaszko, Jacek; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Postoperative atrial fibrillation (POAF) constitutes a common complication in cardiac surgery. POAF develops predominantly after mitral procedures and is associated with increased risk of thromboembolic incidents. The aim of our study was to evaluate the influence of preoperative history of atrial fibrillation on postoperative results in patients submitted to mitral valve repair or replacement. Ninety one patients, hospitalized in Clinic of Cardiac Surgery (Wroclaw Medical University) were enrolled to the study. Patients of mean age 62 ±10 years (53 women, 38 men), with no history of coronary disease, CABG or PCI were included into the study. Two groups were raised: group I – patients with atrial fibrillation on the day of admission or in anamnesis (n = 54, 35 continuous atrial fibrillation, 11 paroxysmal atrial fibrillation, 8 patent atrial fibrillation), group II – patients with undisturbed sinus rhythm and without history of atrial fibrillation (FA). Age and sex distribution did not differ among the groups. In the group I there was a higher incidence of stroke and other thromboembolic incidents (24.1% vs 2.7%; p = 0.01) than in the group II . Severity of mitral regurgitation and left ventricular function on the day of admission were comparable. Type of surgical procedure, complete operative time, aorta cross-clamping time, dose of potassium administered in cardioplegic solution, type of cardioplegia used for cardiac protection, frequency of intraoperative inotropic support, antiarrythmic drugs usage or need for epicardial pacing wires implantation were also comparable. Diameter of left atrium in group I was significantly higher (54.7 ±8.3 vs 50.7 ±8.5; p = 0.02) and the left ventricular end diastolic diameter was smaller (55.1 ±8.8 vs 57.9 ±7.4; p < 0.001). The only factors, which differed in both groups were: positive history of FA and the diameter of left atrium. There was a higher incidence of POAF in group I (66.7% vs 37.8%; p = 0.01), but it did not predict worse postoperative outcome. The frequency of analyzed thromboembolic incidents was comparable. Logistic regression analysis did not reveal any predictive factors for POAF, but it was noted that the age of patients and the left ventricular ejection fraction are important predictive factors for postoperative need of an antiarrythmic drug therapy [OR: 1.05 (95% CI: 1.0–1.11); p = 0.03 and OR: 1.03 (95% CI: 1.0–1.06); p = 0.016]. Diameter of left atrium was an independent predictive factor of brain stroke [OR: 1.16 (95% CI: 0.99–1.35); p = 0.049] and other postoperative thromboembolic incidents [OR: 1.34 (95% CI: 1.03–1.75); p = 0.02]. The type of rhythm on the day of admission in none of the analyzed logistic regression models was an important predictive factor of analyzed end-points. Our data suggest that patients with present sinus rhythm and without history of FA tend to have a comparable risk of postoperative thromboembolic incidents and should be considered candidates for prophylaxis of POAF similarly to patients burdened with the history of FA.